Perception of the injured driver about the factors that influenced in the motorcycle accident - Ana Paula Coelho; Sarah Isabel Magalhães Rios; Sandra Beatriz Pedra Branca Dourado; Vera Lucia Evangelista de Souza Luz; Marylane Viana Veloso; Andreia Karla Carvalho Barbosa Cavalcante (Universidade Federal de Santa Maria, 2017)
Aim: to identify the perception of the injured driver about the factors that influenced the motorcycle accident. Method: a descriptive, qualitative research, developed with fifteen accident victims who were driving the motorcycle at the time of the accident, in September 2015, in the capital of the State of Piaui. Data was analyzed using a thematic analysis. Results: three categories emerged in this study: motorcycle accident victim's perception in relation to their risk behavior; association of the accident to the risky behavior of the other driver and external factors related to the motorcycle accident from the injured driver's perspective. Final thoughts: two great challenges were evidenced: to consolidate a traffic education as effective as the motorcycle sales policy, and the other is to involve society in debates about problems that occur in traffic